“It’s not just the residents who need to be motivated for activity”: a qualitative study of the perspectives of staff on providing activity support for people with psychiatric disabilities in supported housing in Sweden - Brolin, Rosita; Tjörnstrand, Carina; Friis, Mette; Argentzell, Elisabeth; Bejerholm, Ulrika; Eklund, Mona; Brunt, David (Frontiers in Psychiatry, 2024)
Background: The goals for staff in Supported Housing for people with psychiatric disabilities include helping to develop the residents' independence and self-confidence in activities.However, staff have expressed frustration about providing this type of support when motivating residents to engage in meaningful activities and also about the difficulty in finding suitable levels of independence within a housing setting with limitations.Objective: The aim is to explore the views and experiences of housing staff in Supported Housing on how they can stimulate and support engagement in activities for people with psychiatric disabilities.Methods: Twenty-six members of staff infrom twenty supported housing units in ten municipalities in Sweden were interviewed in five focus groups. A semi-structured interview guide was used, and the transcribed material was analyzed using qualitative content analysis.Results: Three main categories emerged from the analysis: Multi-facetedResident-related factors influencing the staff's provision of activity support, Staff's approach for supporting activities, and Staff's struggles to develop their workneeds for supervision and training.Obstacles to participating in activities in the community were identified. Many contrasting factors were found, such as spontaneous or structured activities and individual or group activities, which affected the staff's ability to motivate to activity.A broad approach encompassingincluding in-house training including a focus on values, recruitment policies, staff supervision and interventions focusing on both residents and staff are ways to support staff in motivating residents towards being more active within Supported Housing.